ANALISIS STRATEGI PEMASARAN MENGGUNAKAN METODE SWOT DAN QSPM UNTUK MENINGKATKAN TARGET PENJUALAN (STUDI KASUS: AHASS SUMBER KARYA WONOGIRI) - Nurcahyo, Handika Dwiki; Prasetyo, Rian; Komariah, Ainur (Jurnal Inkofar, 2023)
One of the authorized Honda workshops in Wonogiri Regency, namely Ahass Sumber Karya, based on management data, the target from management in the 2021 period has not reached the target of Ahass Sumber Karya management in 2021. In the period January-December 2021, Ahass Sumber Karya management has a target of 12,220 customers while the actual customers who come to do service are 10,119 customers. The research objectives identify alternative marketing strategies and determine the priority of alternative marketing strategies that management should use to increase the sales target of Ahass Sumber Karya. The method used to determine internal and external marketing strategies through determining the weight of IFE, EFE, IE matrix position, and strategy formulation using the SWOT method. To prioritize alternative marketing strategies using the QSPM method. The research results of the IFE matrix calculation obtained a total IFE score of 3,909 and the EFE matrix calculation obtained a total EFE score of 3,848.The strategy of the IE matrix is described as a growth and development strategy. The SWOT Matrix strategy produces 7 alternatives, namely SO 2 strategies, ST 3 strategies, WO 1 strategy, WT 1. QSPM matrix strategy priority assessment, Ahass Sumber Karya strategy to increase sales target strategy 2 with a TAS score of 4.895, namely improving service quality along with the higher growth of two-wheeled vehicles.